An Introduction to Program Accreditation in Foreign Language Schools in Turkey - Karaferye, Figen (European Journal of Multidisciplinary Studies, 2017)
The aim of this study is to examine the process of accreditation and the widespreadly preferred accreditation institutions in the preparatory programs of universities in Turkey. Accreditation process in English language teaching requires the involvement of all employees in the process from the upper management level to the lower level. It develops and evaluates language teaching in a multifaceted way as physical facilities, education, academic staff and management. Conducting an action research in a preparatory program which is planning to begin an accreditation process is suggested for further research following this review.